Coordination polymers and polygons using di-pyridyl-thiadiazole spacers and substituted phosphorodithioato NiII complexes: potential and limitations for inorganic crystal engineering. Issue 30 (27th June 2016) - Aragoni, M. Carla; Arca, Massimiliano; Coles, Simon J.; Crespo Alonso, Miriam; Coles (née Huth), Susanne L.; Davies, Robert P.; Hursthouse, Michael B.; Isaia, Francesco; Lai, Romina; Lippolis, Vito
Abstract : Differently P-substituted phosphorodithioato Ni II complexes were reacted with bis-pyridyl thiadiazole spacersL1 andL2 obtaining either polymeric or discrete supramolecular constructs. Abstract : Coordinatively unsaturated P-substituted dithiophosphonato, dithiophosphato, and dithiophosphito complexes {[Ni((MeO)2 PS2 )2 ] (1 ), [Ni((EtO)2 PS2 )2 ] (2 ), [Ni(MeOdtp)2 ] (3 ), and [Ni((Ph)2 PS2 )2 ] (4 )} were reacted with the bis-functional ligands 3, 5-di-(4-pyridyl)-1, 2, 4-thiadiazole (L1 ) and 3, 5-di-(3-pyridyl)-1, 2, 4-thiadiazole (L2 ) to give the coordination polymers (1–4 ·L1 )∞, (3 ·L2 )∞, and (4 ·L2 ·2C7 H8 )∞ and the discrete dimers (1–2 ·L2 )2, all characterised by single crystal X-ray diffraction. A comparison of the structures shows thatL1 can be exploited for the predictable assembly of undulating chains independent of the nature of the Ni II complex, whileL2 allows for the existence of different supramolecular constructs ensuing from different ligand conformations deriving from the rotation of the pyridyl rings.